Autophagy Is Impaired in Neutrophils from Streptozotocin-Induced Diabetic Rats - Kuwabara, Wilson Mitsuo Tatagiba; Curi, Rui; Alba-Loureiro, Tatiana Carolina (Frontiers in Immunology, 2017)
We tested the hypothesis that changes reported on functions of neutrophils from streptozotocin-induced diabetic rats involve autophagy impairment. Wistar rats were rendered diabetic by streptozotocin injection (65 mg/kg, i.v.), and the measurements were carried out 2 weeks afterward. Neutrophils were collected through intraperitoneal cavity lavage after 4 h of i.p. oyster glycogen type 2 injection. Neutrophils cultured with PMA (20 nM) for 1 h were used for analysis of plasma membrane integrity, DNA fragmentation, and mitochondrial depolarization by flow cytometry; expression of Atg5, Atg14, Beclin1, LC3BII, and Rab9 by RT-PCR; the contents of caspase 3, LC3BII/LC3BI, and pS6 by western blotting; ATP content by fluorescence essay; reactive oxygen species production by chemiluminescence (Luminol), and autophagy by immunofluorescence tracking LC3B cleavage. Herein, neutrophils from diabetic rats had high DNA fragmentation, depolarization of mitochondrial membrane, low content of ATP, and high content of cleaved caspase 3 after PMA stimulation. Neutrophils from diabetic rats also had low expression of LC3B, failed to increase the expression of Rab9 and Atg14 induced by PMA stimulation. Neutrophils from diabetic animals also had low cleavage of LC3BI to LC3BII and do not present punctate structures that label autophagosomal membranes after stimulus. The changes of neutrophil function reported in diabetic rats do involve impaired autophagy. The suppression of autophagy in neutrophils from diabetic rats may be associated with the activation of the mTOR signaling as indicated by the high content of pS6.